Thermography in Bike Fitting: A Literature Review - Warre Clarys; Oscar Vallet; Jan Verstockt; Hai Zhang; Simon Verspeek; Gunther Steenackers (Sensors)
Cycling comfort significantly impacts both enjoyment and performance, with discomfort potentially leading to injuries. Traditional bike-fitting methods, while effective for biomechanical adjustments, often overlook physiological responses such as pressure distribution and asymmetry. Infrared thermography (IRT), a non-invasive technique analyzing surface temperature variations, offers the potential to enhance bike fitting by identifying pressure points, asymmetries, and discomfort zones. This review evaluates the application of IRT in bike fitting, highlighting its ability to provide objective, real-time insights into cyclist comfort and injury prevention. However, limitations such as variability in thermographic protocols and the lack of standardized methodologies necessitate further research. By addressing these gaps, IRT could transform bike fitting into a more precise, personalized, and effective practice for cyclists across all levels.